1994
DOI: 10.3109/03630269409014142
|View full text |Cite
|
Sign up to set email alerts
|

Hb Footscray or α133(H16) SER→ARG: A New Hemoglobin Variant

Abstract: Hb Footscray, alpha 133(H16) Ser-->Arg, is a newly described hemoglobin variant found in an adult male of Polish-Hungarian descent. Hematological data and stability by the isopropanol stability test were normal. The abnormal hemoglobin comprised 15% of total hemoglobin and migrated as a split band in the Hb F position on cellulose acetate at pH 8.6. Like Hb Manitoba, which is also a Ser-->Arg mutation and occurs in a very similar spatial position, the split bands presumably arise from the formation of asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Examination of multiple traces showed that the absorbance ratio of 415:280nm for the HbA 0 peak was 3.0 while that for X and Y were 3.0 and 3.1 respectively indicating that both X and Y had the same number of heme groups per chain as each other and the same number as HbA. Several Hb variants, like Manitoba (αS102R) and Footscray (αS133R), which would be expected to give single variant bands in the HbS position on electrophoresis at pH 8.6, actually migrate as paired bands between HbS and HbF [13]. This is due to an alteration in the equilibrium constant between dimer (αβ) and tetramer (αβ) 2 which results in an additional mixed hybrid band (α A α X β 2 ).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Examination of multiple traces showed that the absorbance ratio of 415:280nm for the HbA 0 peak was 3.0 while that for X and Y were 3.0 and 3.1 respectively indicating that both X and Y had the same number of heme groups per chain as each other and the same number as HbA. Several Hb variants, like Manitoba (αS102R) and Footscray (αS133R), which would be expected to give single variant bands in the HbS position on electrophoresis at pH 8.6, actually migrate as paired bands between HbS and HbF [13]. This is due to an alteration in the equilibrium constant between dimer (αβ) and tetramer (αβ) 2 which results in an additional mixed hybrid band (α A α X β 2 ).…”
Section: Resultsmentioning
confidence: 89%
“…Another possible explanation was the detection of mixed hybrids due to an alteration in the dimer (αβ) tetramer (αβ) 2 equilibrium constant. This could result in the generation of additional stabilised asymmetric hybrids (α A α L β 2 ), as have been seen with other Hb variants [13]. However when both X and Y were purified and reanalysed by cation exchange HPLC, they were found to be non-inter convertible with each other.…”
Section: Discussionmentioning
confidence: 84%
“…The analysis of the hemoglobins and polypeptide chains in the electrophoretic profiles under different pH conditions, and the chromatographic profiles presented by the sample, allowed us to identify Hb Val de Marne and compare the results with other studies that have indicated this Hb variant in other populations (Wajcman et al, 1993;Owen and Hendy, 1994;Ma et al, 2004;Akbari and Hamid, 2012). Wajcman et al (1993) first described the Hb VM variant in a French family during a neonatal hemoglobinopathy screening program.…”
Section: Discussionmentioning
confidence: 99%
“…Val de Marne is a rare Hb variant and has been described in only four families throughout the world, the first report being in 1993 in France (Wajcman et al, 1993), followed by Australia (Owen and Hendy, 1994), China (Ma et al, 2004), and Iran (Akbari and Hamid, 2012). The terms Hb Val de Marne (Hb VM) and Hb Footscray derive from the regions where this variant was first described.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation